Educational philosophy of Abu Hassan Al-Amiri - Talib, Marwa Ali; Alshimari, Abdulkareem Salman (Al-Adab Journal, 2023)
The Imam began his study of this issue by defining a goal, which is to explain the virtue of Islam in relation to other religions, and he paved the way for this by classifying the sciences into religious and legal sciences, then reconciled between them, then he demonstrated the superiority of religious sciences over legal sciences.Al-Amiri’s philosophy, while studying this issue, was distinguished by the integrative view of the sciences, whether those affiliated with wisdom or affiliated with the religion, as I see that they are integrated to achieve the general goal of it, and therefore Al-Amiri responded to the owners of some sciences who challenged other sciences and underestimated their importance.Al-Amiri concluded his effort in this case by responding to the suspicions that are raised against Islam, and he had his methodology in analyzing and refuting these suspicions in proportion to his being a philosopher.Therefore, I wanted to discuss this aspect of the philosophy of Abu al-Hasan al-Amiri, methodological research, meaning that we focus on al-Amiri's approach, whether in his classification of sciences or his statement of the virtues of Islam or in his response to the suspicions that are raised against Islam.